Ground‐Based Magnetometer Response to Impacting Magnetosheath Jets. Issue 8 (29th July 2021) - Norenius, L.; Hamrin, M.; Goncharov, O.; Gunell, H.; Opgenoorth, H.; Pitkänen, T.; Chong, S.; Partamies, N.; Baddeley, L.
Abstract: Localized dynamic pressure pulses in the magnetosheath, or jets, have been a popular topic for discussion in recent decades. Studies show that they can propagate through the magnetosheath and impact the magnetopause, possibly showing up as geoeffective elements at ground level. However, questions still remain on how geoeffective they can be. Previous studies have been limited to case studies during few days and with only a handful of events. In this study we have found 65 cases of impacting jets using observations from the Multiscale Magnetospheric mission during 2015–2017. We examine their geoeffectiveness using ground‐based magnetometers (GMAGs). From our statistics we find that GMAGs observe responses as fluctuations in the geomagnetic field with amplitudes of 34 nT, frequencies of 1.9 mHz, and damping times of 370 s. Further, the parallel length and the maximum dynamic pressure of the jet dictate the amplitude of the observed GMAG response. Longer and higher pressure jets inducing larger amplitude responses in GMAG horizontal components. The median time required for the signal to be detected by GMAGs is 190 s. We also examine if jets can be harmful for human infrastructure and cannot exclude that such events could exist. Key Points: Ground‐based magnetometers observe damped oscillations resulting from impacting jets The median damping time and observed frequency is 370 s and 1.9 mHz respectively We suggest that larger and more energetic jets might increase the amplitude of the ground‐based magnetic response